Pengaruh Penggunaan Jet Ranger dan Kuantitas Udara Masuk terhadap Daya Sepeda Motor 150cc - Rangga Retiadji Prasetyawan; Khambali Khambali; Yuniarto Agus Winoko; Bagus Wahyudi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Motorcycle engine performance is highly dependent on the air intake system, which plays a crucial role in the combustion process. One common method for improving engine performance is modifying the intake system, either by installing additional devices or adjusting the quantity of incoming air. One innovation that is starting to be widely used is the Jet Ranger, an additional device on the intake duct that is claimed to be able to increase air flow into the combustion chamber. This study aims to determine the effect of the use of Jet Ranger and variations in the quantity of incoming air on the maximum power of a 150 cc motorcycle engine, as well as to analyze the interaction between the two variables. The study was conducted using an experimental method with a two-way factorial approach. The independent variables in this study consisted of two factors, namely the use of Jet Ranger (without Jet Ranger and with Jet Ranger) and variations in the quantity of incoming air divided into four levels (0.008; 0.012; 0.016; and 0.020 kg/s). Maximum power testing was conducted using a Leads dynotest, while the mass of incoming air was calculated based on air velocity measured using a digital anemometer. The test data were statistically analyzed using a two-way ANOVA to identify the effect of each factor and the interaction between them on engine power. The results of the study indicate that the use of Jet Ranger significantly increases engine power. Variations in the quantity of intake air also significantly affect the power generated. In addition, the interaction between the use of Jet Ranger and the quantity of intake air is proven to have a significant impact on increasing the maximum engine power. These results are in line with the theory of intake systems which states that increasing optimal air flow can increase the volumetric efficiency of the engine, and are supported by findings from previous studies. Therefore, these findings can be used as a reference in the development of air intake systems on motorcycles to achieve more optimal engine performance.